Perspectives in business informatics research : 13th International Conference, BIR 2014, Lund, Sweden, September 22-24, 2014. Proceedings - Andersson, Bo; Holmberg, Nicklas; Johansson, Bjorn (Lecture Notes in Business Information Processing, 2014)
This book constitutes the proceedings of the 13th International Conference on Perspectives in Business Informatics Research, BIR 2014, held in Lund, Sweden, in September 2014. Overall, 71 submissions were rigorously reviewed by 55 members of the Program Committee representing 22 countries. As a result, 27 full papers have been selected for publication in this volume. The papers cover many aspects of business information research and have been organized in topical sections on: business, people, and systems; business and information systems development; and contextualized evaluation of business informatics.